Asphaltenes and preasphaltenes from coal liquid extracts: feedstocks to obtain carbon mesophase - Juan Barraza; Natalia Muñoz; Lina Barona (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
The aim of this work was to produce mesophase by using preasphaltenes and asphaltenes from coal liquid extracts obtained in a Direct Coal Liquefaction (DCL)  process.  Preasphaltenes  and  asphaltenes  were  carbonized  at  inert  atmosphere  at  temperatures  of  350,  400  and  450  °C  during  180  min.  The  mesophase identification and quantification was performed by polarized light microscopy. The results showed that the highest concentration of mesophase (79% v/v), with mass yield of 12,4% w/w, was obtained from the asphaltenes treated at 400 °C. The highest mesophase global yield (with respect to coal fed) was 4,4% w/w.